The impact of comparative education research on institutional theory - Baker, David, 1952 Jan. 5-; Wiseman, Alexander W., 1968- (International perspectives on education and society ;, 2006)
This volume of "International Perspectives on Education and Society" explores how educational research from a comparative perspective has been instrumental in broadening and testing hypotheses from institutional theory. Institutional theory has also played an increasingly influential role in developing an understanding of education in society. This symbiotic relationship has proven intellectually productive. In light of the impact that comparative education research has had on institutional theory, the chapters in this volume ask where the comparative and international study of education as an institution is heading in the 21st century. Chapters range from theoretical discussions of the impact that comparative research has had on institutional theory to highly empirical comparative scholarship that tests basic institutional assumptions and trends. Two pioneers in the field, John W. Meyer and Francisco O. Ramirez, contribute the Forward and the concluding chapter. In addition to the editors, other contributors to this volume include M. Fernanda Astiz, Janice Aurini, Jason Beech, Edward F. Bodine, Karen Bradley, Claudia Buchmann, Scott Davies, Gili S. Drori, David H. Kamens, Jong-Seon Kim, Hyeyoung Moon, Hyunjoon Park, Emilio A. Parrado, Lauren Rauscher, John G. Richardson, David F. Suarez, and Regina E. Werum.